Decentralized Decision-making in Schools : The Theory and Evidence on School-based Management - Barrera-Osorio, Felipe; Fasih, Tazeen; Patrinos, Harry Anthony; Santibáñez, Lucrecia (World Bank, 2012)
The school-based management (SBM) has become a very popular movement over the last decade. The World Bank's work on school-based management emerged from a need to better define the concept, review the evidence, support impact assessments in various countries, and provide feedback to project teams. The authors took detailed stock of the existing literature on school-based management and then identified several cases that the Bank was supporting in various countries. The authors present as well general guidance on how to evaluate school-based management programs. The Bank continues to support and oversee a number of impact evaluations of school-based management programs in an array of countries. Despite the clear commitment of governments and international agencies to the education sector, efficient, and equitable access remains elusive for many populations - especially for girls, indigenous peoples, and other poor and marginalized groups. Many international initiatives focus on these access issues with great commitment, but even where the vast majority of children do have access to education facilities, the quality of that education often is very poor. This fact increasingly is apparent in the scores from international learning assessments on which most students from developing countries do not excel. Evidence has shown that merely increasing resource allocation without also introducing institutional reforms in the education sector will not increase equity or improve the quality of education. One way to decentralize decision-making power in education is known popularly as SBM. There are other names for this concept, but they all refer to the decentralization of authority from the central government to the school level. SBM emphasizes the individual school (represented by any combination of principals, teachers, parents, students, and other members of the school community) as the main decision-making authority, and holds that this shift in the formulating of decisions will lead to improvement in the delivery of education.